PERAN PEKERJA SOSIAL DALAM MENGATASI PERMASALAHAN IBU YANG BERCERAI (STUDI KASUS DI RW 010 KELURAHAN SUKABUMI UTARA, JAKARTA BARAT) - Jazilah, Jazilah; Mayaut, Flores George; Ifan, Maykel (Jurnal Insani, 2024)
This study highlights the social problems experienced by post-divorce mothers, and finds out the role of social workers in providing social interventions to divorced mothers. The method used is qualitative which is descriptive analytical. The determination of cases uses purposive sampling by assigning 3 cases. Data collection techniques are carried out through observation, interviews, and documentation studies. The results of the study show that: 1) the problems experienced by divorced mothers include economic difficulties, childcare, mental health, conflicts with ex-husbands, conflicts with parents and extended family, lack of confidence because they have been seduced, and lack of motivation. The role of social workers in handling the problem of divorced mothers in the RW 010 area, North Sukabumi sub-district includes: carrying out home visits, providing motivation, providing assistance and education with family members where the client lives. After getting the intervention, the client is excited to continue living and returning to work; conflicts with the family have decreased; become more attentive to children and start socializing with neighbors. As for the suggestion, for the RW 010 area to pay more attention to divorced mothers being involved in community activities. Clients who divorced mothers are more active and productive and eager to continue their lives and maintain good relationships with their children, family, and the surrounding environment. Because a good healthy environment can help restore mental health.